Macroeconomic Electric Energy Production Efficiency of Photovoltaic Panels in Single-Family Homes in Poland - Marcin Bukowski; Janusz Majewski; Agnieszka Sobolewska (Energies, 2020)
An increase in energy demand that is caused by fast economic development, a limited and constantly decreasing supply of traditional energy sources, as well as excessive environmental pollution that is caused by an increasing concentration of dust and gases in the atmosphere constitute the main factors that contribute to the ever-increasing interest in renewable sources of energy. The most important and promising renewable source of energy is thought to be solar energy. The aim of the paper is to assess the macroeconomic investment efficiency of photovoltaic installations in order to meet the demand for electric energy in single-family homes in Polish conditions. The conducted analysis comprises market characteristics and legal regulations concerning the sale of electric energy in Poland. Calculations were made for 320 variants that differed with regard to investment location, building orientation, and roof inclination. The results indicate that the most beneficial region for photovoltaic micro-installations, from a social perspective, is the south-east of and central Poland. The highest values of economic efficiency were achieved in the case of a southern roof inclination as well as a south-eastern and south-western building orientation. No big differences were observed in the economic investment efficiency for the panel inclinations. The calculated Discounted Payback Period, depending on the calculation method, equals 5.4 to 10 years. The results of the study confirm that the implemented support instruments for investments in photovoltaic installations producing energy for single-family house demand is economically viable.